O Novo Marco Legal do Saneamento Básico (Lei nº 14.026, de 15 de julho de 2020): entrelaçamentos e desafios para a efetivação da meta de universalização dos serviços públicos de saneamento até 2033. - Arruda, Thaise (2023)
The present study aimed to analyze the public basic sanitation policy implemented by Law nº 14,026, of July 15, 2020, and the intertwining for the realization of the goal of universalization of public sanitation services by 2033 and the promotion of the recommended sustainable development by Agenda 2030 and SDG 6. Basic sanitation integrates a set of public infrastructure services ranging from the supply of drinking water; sanitary sewage, urban cleaning and solid waste management; drainage and management of urban rainwater, the elements become relevant for the achievement of goals, in addition to the careful regulation to be carried out by the responsible regulatory entities. In order to achieve the objectives, exploratory and descriptive research with a qualitative approach was adopted as a methodological procedure in the analysis of data in relation to public sanitation policy, through primary and secondary sources, including bibliographical review, doctrine, Brazilian legislation and documental study. The results of the research indicate that, given the scenario presented, it signals a low performance of the sustainable development indicators, there is no envisioning of an efficient state public policy for basic sanitation that can guide the search for the universalization of Law nº 14.026/2020, with goal to be achieved by the year 2033, consequently negatively affects the entire set of implementation of the SDGs, especially SDG 6 that make up the 2030 Agenda. of urban development in the perspective of fulfilling the goals set forth by the new law to make the right to basic sanitation universal, in addition to the careful regulation to be carried out and the periodic evaluation of the effectiveness of the legal instruments brought by the new legal framework, in the promotion of actions for the reduction of socio-environmental inequalities.